Identification and characterization of Tc1/ mariner-like DNA transposons in genomes of the pathogenic fungi of the Paracoccidioides species complex - Marini, Marjorie Mendes (2010)
Background: Paracoccidioides brasiliensis (Eukaryota, Fungi, Ascomycota) is a thermodimorphic fungus, the etiological agent of paracoccidioidomycosis, the most important systemic mycoses in Latin America. Three isolates corresponding to distinct phylogenetic lineages of the Paracoccidioides species complex had their genomes sequenced. In this study the identification and characterization of class II transposable elements in the genomes of these fungi was carried out. Results: A genomic survey for DNA transposons in the sequence assemblies of Paracoccidioides, a genus recently proposed to encompass species P. brasiliensis (harboring phylogenetic lineages S1, PS2, PS3) and P. lutzii (Pb01-like isolates), has been completed. Eight new Tc1/mariner families, referred to as Trem (Transposable element mariner), labeled A through H were identified. Elements from each family have 65-80% sequence similarity with other Tc1/mariner elements. They are flanked by 2-bp TA target site duplications and different termini. Encoded DDD-transposases, some of which have complete ORFs, indicated that they could be functionally active. The distribution of Trem elements varied between the genomic sequences characterized as belonging to P. brasiliensis (S1 and PS2) and P. lutzii. TremC and H elements would have been present in a hypothetical ancestor common to P. brasiliensis and P. lutzii, while TremA, B and F elements were either acquired by P. brasiliensis or lost by P. lutzii after speciation. Although TremD and TremE share about 70% similarity, they are specific to P. brasiliensis and P. lutzii, respectively. This suggests that these elements could either have been present in a hypothetical common ancestor and have evolved divergently after the split between P. brasiliensis and P. Lutzii, or have been independently acquired by horizontal transfer. Conclusions: New families of Tc1/mariner DNA transposons in the genomic assemblies of the Paracoccidioides species complex are described. Families were distinguished based on significant BLAST identities between transposases and/or TIRs. The expansion of Trem in a putative ancestor common to the species P. brasiliensis and P. lutzii would have given origin to TremC and TremH, while other elements could have been acquired or lost after speciation had occurred. The results may contribute to our understanding of the organization and architecture of genomes in the genus Paracoccidioides.